STUDY OF PHENOTYPIC AND GENETIC DIVERSITY IN CLUSTER BEAN(CYAMOPSISTETRAGONOLOBA[L.]TAUB) GENOTYPES BY RAPD & ISSR MARKERS - Ragula Seenaiah1*, Palakurthi Ramesh2, Banavath Jayanna Naik3, Panditi Varakumar4, Akila ChandraSekhar5, Puli Chandra Obul reddy6, Thimma Naik7 (Chelonian Research Foundation, 2023)
Molecular markers are one of the most important tools for evaluating genetic diversity and genotypic identification was used in a plant breeding program. These are the major source for genetic predictability for breeding and crop improvement in Cluster bean (Cyamopsistetragonoaloba [L.]Taub). The present study deals with the genetic diversity in 22 genotypes of Cluster bean seeds collected from different states in India. The different genotypes were characterized for morphological traits and molecular analysis were performed using seven Randomly Amplified Polymorphic DNA (RAPD) and four Inter Simple Sequence Repeat (ISSR) molecular markers. Total 31 Amplicon pattern was obtained by RAPD primers. Among the four ISSR primers, UBC-819 produced the highest number of banding pattern. Word's Elucidean-Distances tree was constructed with RAPD and ISSR data. The genetic diversity and phenotypic distance was analyzed by words elucidation distance was genotypically 0.4 – 0.92 and phenotypic distance range from 0-300 was observed. Keywords: Molecular markers, Cluster bean, RAPD, ISSR, Polymorphism